Electrospun PET/Ag nanofiber filter membrane preparation and performance research for individual dust protection - Qian ZHANG; Haizhou SONG; Feng SU; Jinguo LIU; Zhuo XU (Meikuang Anquan)
The PET/Ag nanofibrous membrane, added antibacterial silver ions, was prepared by electrospinning technology with polyethylene terephthalate as the raw material, dissolved in the mixed solvent of trifluoroacetic acid and dichloromethane. Scanning electron microscopy (SEM) and X-ray photoelectron spectroscopy (XPS) were used to characterize the morphologies and elements of the nanofibrous membrane. The comprehensive protection performance was tested by contact angle test, moisture permeability test, filtration test and antibacterial test. The results show that the fiber diameter of the nanofiber membrane can be effectively controlled by adjusting the mass fraction of the spinning solution, but the shape of the fiber diameter is almost unaffected; materials with different filtering effects on particulate matter can be obtained by controlling the spinning time; when the spinning solution mass fraction was 10% and the spinning time was 2 h, the PET nanofibrous membrane had the highest quality factor (0.041 Pa−1) and the best comprehensive protection performance. Under this condition, the water vapor permeability of the nanofibrous membrane was 7 101.37 (g/m2·d), and it had strong hydrophobicity. It also inhibits Escherichia coli and Staphylococcus aureus.